PROMOTING NEW AGRICULTURAL TECHNOLOGY ADAPTATION: A REVIEW OF THEORETICAL AND PRACTICAL ISSUES, AND SOLUTIONS FOR VEGETABLE FARMERS IN SVAY RIENG PROVINCE, CAMBODIA - Chhun, Hong; Borarin, Buntong; Mardy, Serey; Bunyeth, Chan; Vibol, Sao (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
An idea for sustainable agricultural development, new agricultural technology adaptation (NATA) in agricultural production helps overcome problems in agricultural production by utilizing the best aspects of technology application. In order to identify the obstacles and suggest some solutions for improving the NATA in agricultural production in Cambodia in the future, this research reviewed theoretical and practical difficulties on boosting NATA in Svay Rieng province. The study demonstrated that the NATA application in agricultural production is an unavoidable route for the agriculture sector development in Svay Rieng under the context of global integration and impacts of the industry revolution 4.0. This was based on secondary information and data from published papers and documents. Thus, the Cambodian government has recently given close attention to NATA promotion in agricultural output. Despite the impressive accomplishments, there are currently few businesses and farm households using NATA in agricultural output, and NATA growth in Svay Rieng still confronts many obstacles. Improving the current policy structure is essential for raising the NATA in agricultural output in Svay Rieng. Additionally, in the near future in Svay Rieng province, NATA application implementation, NATA development and planning, human resource training, credit assistance, and propaganda on the NATA's effectiveness in agricultural production should all be strengthened.